BLACK BOX TESTING PADA GAME ANIMASI 2D ‘OSKAR ADVENTURE’ - Septilia Arfida; Hariyanto Wibowo; Gusnanda Oskar (Journal of Innovation Research and Knowledge, 2026)
Abstract: Rapid technological advancement has influenced various sectors, including education. One innovation in education is the development of educational games that combine learning materials with entertainment elements, making the learning process more engaging, interactive, and easier to understand. In today's digital era, many children spend more time playing entertainment-based games that do not contribute significantly to improving knowledge or skills. This condition may affect children's learning motivation, as their attention tends to focus more on gaming activities rather than learning activities. Therefore, the development of educational games has become an alternative learning medium that balances entertainment and educational content. This research focuses on the implementation of the Black Box Testing method on the 2D animation game “Oskar Adventure” as an interactive learning medium. Testing was conducted to ensure that every function in the game operated according to the designed requirements and objectives. The game was developed by integrating educational materials into gameplay so that children could gain a more engaging and enjoyable learning experience. The testing results showed that all game features functioned properly as expected. Furthermore, the 2D animation game “Oskar Adventure” can serve as an alternative learning medium that enhances learning interest while providing an educational gaming experience.